WILLINGNESS TO PAY (WTP) JASA LINGKUNGAN SUMBERDAYA AIR TANAH SUMUR DI KOTA KUPANG - Aplonia Bani; Fredrik Benu; Herry Kotta (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2020)
Abstract: This study using an interview for survey, respondents were asked a series of questions about their willingness to pay for environmental services as hypothetical research, which would assist in the conservation of water resources. Willingness to pay (WTP) for the owners who commercialized the well water using bidding game methods with offers of different starting points was asked to the respondents for the Groundwater Basin (CAT) Tabun-Bakunase-Haukoto-Sikumana, CAT Kupang-Oesapa-Tarus, CAT Penfui and Baumata, CAT Bolok-Tenau-Alak-Namosain. The results of the study showed that the value of Willingnes To Pay of the well owner was commercialized from 17 respondents who were willing to pay in the amount of Rp. 518.209 or Rp.6,100/m3. The average cost of production around Rp. 146.650/day, with the amount of discharged water that taken is 4.175 m3, with a cost per 5 m3 is Rp. 3.482, resulting in Rp.30.997 surplus for the producer. Consumer Respondent surplus towards payment of environmental services for commercialized wells water resources is Rp. 496.000,. The consumption of commercialized well water resources in Kupang on CAT Bolok-Tenau-Alak-Namosain is 150 m3/day or 54.750 m3/year, CAT Tabun-Bakunase-Haukoto-Sikumana is 2.600 m3/day or 949.000 m3/year, CAT Kupang- Oesapa-Tarus is 1.125 m3/day or 410.625 m3/year, CAT Penfui is 300 m3/day or 109.500 m3/year, and the amount of water withdrawal is less than the potential of groundwater in each CAT, so there is a surplus of water discharge that taken on CAT in the city of Kupang. The factors that influence the agreed response based on the test results indicate that the risk factors that have a low level of risk are Age (X1), Education (X2), Occupation (X3), Cost (X5), while risk factors that have a strong level of risk are Acceptance (X4) and Environmental Services Knowledge (X6). For Age risk factors (X1), Education (X2), Employment (X3), Costs (X5) have a low level risk level, this means that these factors are not risk factors that can pose a high risk on the willingness of the respondents to pay (WTP). While Acceptance (X4) and Environmental Services Knowledge (X6) have strong risk factors which means that these factors pose a strong risk to the willingness of respondents to pay (WTP), so that a significant effect is partially between acceptance and knowledge of environmental services to willingness of well owners in paying for groundwater environmental services that are used as economic goods. Acceptance and knowledge of environmental services have a significant effect because the greater the acceptance and knowledge of environmental services, the greater the willingness to pay for environmental services.